BLOOD PRESSURE (BP) AND WHITE MATTER CHANGES IN TIA AND STROKE PATIENTS: ASSOCIATION WITH LONG-TERM MEAN BP VERSUS VARIABILITY. (29th November 2012) - Simoni, M; Li, L; Mehta, Z; Rothwell, P
Abstract : Background: White matter changes (WMC) on brain imaging, reflecting chronic subcortical ischaemia, increase steeply with age. Hypertension is a risk factor for WMC, particularly in younger patients, and variability in blood pressure (BP) is a risk factor for acute stroke. However, the relative contribution of long-term mean BP versus BP variability to the development of WMC is uncertain. We determined these associations based on all BP measures over a 10-year period. Methods: In consecutive TIA or stroke patients, we collected all pre-morbid BPs from primary care. We rated WMC on CT or MRI with four scales, and calculated their age-specific associations with 10-year measurements of BP parameters (mean systolic and diastolic BP and average visit-to-visit variability ie, the mean difference between successive measures). Results: 520 MRI and 1717 CT were assessed. Results were similar for CT and MRI and for different WMC scales. 10-year mean SBP was strongly associated with WMC at age <65 years (OR, 95% CI, per 10 mm Hg SBP and van Swieten scale—1.37, 1.12–1.68, p=0 .002), but the association diminished with age. 10-year mean DBP was associated with WMC at all ages (OR/10 mm Hg=1.50, 1.26–1.77, p<0.0001). Variability in SBP or DBP was not associated with WMC at any age. Conclusions: Increased 10-year mean SBP and DBP were associated with WMC, but we found no association with BP variability, consistent with the hypothesis that raised long-term mean BP results in chronic subcortical ischaemia whereas variability in BP is associated with an increased risk of acute events.